Kajian Sifat Enjiniring Puree Wortel (Daucus carrota L.) - Nanda Ikhtiar Muti; Dian Purbasari (Jurnal Agritechno, 2021)
The Post-harvest processing of carrots in Indonesia is still limited to being processed into the main ingredients of soup or vegetable of cap cay and sometimes blended to drink as juice and currently, there are still trying to make flour from carrots. This study uses a Complete Randomized Design (RAL) with two factors, namely the comparison of carrots and water and the length of grinding time. The measurement stages of technical properties begin from the preparation of raw materials, washing, cutting, purification, then measured of technical properties. The technical properties measured are viscosity, total solids, density, color, and thermal conductivity. The comparison of carrots and water used are 3:1 (450 gr:150 ml), 2:1 (400 gr:200 ml), and 1:2 (200 gr:400 ml) for a long time period of 150 seconds, 210 seconds, and 270 seconds. The Data analysis using two-way ANOVA statistical test with two factors that affect the comparison of carrots and water and length of life. Viscosity values range from 1697.78 cP to 4661.44 cP. The total value of solids ranges from 3.11% to 7.20%. Density values range from 1,004 g/ml to 1,015 g/ml. The L color index value ranges from 34.33 to 42.77. Color index values range from -1.06 to 6.44. The color index value b ranges from 12.65 to 26.95. Thermal conductivity values range from 0.577 W/m.K to 0.682 W/m.K. The more proportions of carrots in a puree solution, the higher of viscosity value, total solids, density, and color indexes L, a, and b. While the value of thermal conductivity does not affect the comparison of carrots and water. At purification, time treatment does not affect solid total values, color index values L, a, and b. However, it affects the density and viscosity value of carrot puree. The longer the milling time, the greater the viscosity value and density.